Metode Ilmiah dalam Filsafat Ilmu : Suatu Analisis tentang Alur Pikir Filosofis dalam Penelitian - Vanila Nur Sela (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The scientific method is an important part of the philosophy of science because it is the basis for obtaining rational, systematic, and accountable knowledge. This research aims to analyze scientific methods from the perspective of the philosophy of science and to examine the philosophical thought processes underlying the research process. The study uses a library research method with a literature review approach. Data are obtained from various scientific articles, books, and relevant academic sources, then analyzed qualitatively through the stages of data identification, classification, synthesis, and interpretation. Although the scientific method has been widely used in research, its understanding is still often limited to procedural and technical aspects. As a result, the philosophical dimensions underlying the research process, such as ontological, epistemological, and axiological aspects, often receive less attention. Philosophical thought processes in research are reflected through the use of logic and inductive, deductive, and abductive reasoning in constructing knowledge. The development of the scientific method is also influenced by Karl Popper's thoughts on falsification and Thomas S. Kuhn's thoughts on paradigm shift, which demonstrate that scientific truth is dynamic and open to criticism. Thus, the scientific method not only functions as a research guideline, but also as a rational, critical, reflective and ethical framework for producing knowledge that is beneficial to human life.